Nocardia brasiliensis Infection Complicating Cryptogenic Organizing Pneumonia. (28th February 2017) - Fernandes, Alison M.; Sluzevich, Jason C.; Mira-Avendano, Isabel
Abstract : Pulmonary nocardiosis is a severe and uncommon opportunistic infection caused by Nocardia species. We present a patient with cryptogenic organizing pneumonia who was receiving long-term immunosuppressive therapy, whose treatment course was complicated by cutaneous and pulmonary nocardiosis. Tissue cultures confirmed Nocardia brasiliensis . Nocardiosis should be a diagnostic consideration for patients treated with long-term immunosuppression who have worsening pulmonary symptoms and relapsing pustular skin lesions.